2020
DOI: 10.4102/hsag.v25i0.1345
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of registered nurses in a private critical care unit in the Eastern Cape: A pilot study

Abstract: Background Job satisfaction is influenced by factors that are interpersonal (between nurse and colleagues), intrapersonal (within the nurse) and extra-personal (external to the nurse). Aim The primary objective of this study was to explore and describe factors influencing the job satisfaction of registered nurses in a particular private critical care unit. The second objective was to make recommendations to enhance the job satisfaction of registered nurses in this priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This study revealed that health extension workers who received stimulating recognition from management were more satisfied with their job compared to their counterparts. This finding was in line with studies carried out in East Shewa Zone of Oromia Region, 33 Harar City, 26 West Ethiopia, 35 and Northern Ethiopia, 37 public health facilities of Ethiopia, 29 Kenya, 41 Eastern Cape, 42 and Iran. 43 This could be explained as recognition has the potential to motivate the HEWs, enhance their skills, create a good attitude toward achieving the common organizational goal, and finally make HEWs more likely satisfied.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that health extension workers who received stimulating recognition from management were more satisfied with their job compared to their counterparts. This finding was in line with studies carried out in East Shewa Zone of Oromia Region, 33 Harar City, 26 West Ethiopia, 35 and Northern Ethiopia, 37 public health facilities of Ethiopia, 29 Kenya, 41 Eastern Cape, 42 and Iran. 43 This could be explained as recognition has the potential to motivate the HEWs, enhance their skills, create a good attitude toward achieving the common organizational goal, and finally make HEWs more likely satisfied.…”
Section: Discussionsupporting
confidence: 91%
“…Two of the criteria for spiritual factors are quality of work life and feeling of comfort in the workplace, although several studies have revealed that nurses neither have a good quality of work life nor do they enjoy enough comfort (21)(22)(23). In the study by Morton et al, however, most nurses were discovered to feel comfortable in their work environment (24). In our study, the matrix of pairwise comparisons of material factors showed an incompatibility rate of IR = 0.02, which was acceptable and, therefore, eliminating incompatibility was not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-level relationship may increase job satisfaction and performance, while group-level relationship may weaken employees' sense of procedural justice and reduce their work performance [33]. Relationship with supervisors and colleagues has been estimated to have significant influence on job satisfaction in different fields such as healthcare industry [34]. Employees who are from dominant groups in the organization tend to be more satisfied with their jobs because their managers and coworkers tend to provide them with more feedback and support [35].…”
Section: Interpersonal Relationshipmentioning
confidence: 99%